Social Hormones and Human Behavior: What Do We Know and Where Do We Go from Here - Richard Paul Ebstein (Frontiers Research Topics, 2015)
Oxytocin (OT) and arginine vasopressin (AVP) are the paramount social hormones in mammals and accumulating evidence also strengthens the unique role of these neuropeptides also in human social behavior. Indeed from voles to humans, OT and AVP modulate an intriguing number of social behaviors resonating across species such as the quality of pair bonding, parenting, modulations of social stress, in-group & out-group relationships and social communications. Recent molecular genetic studies of the oxytocin (OXTR), arginine vasopressin 1a (AVPR1a) and arginine vasopressin 1b (AVPR1b) receptors have strengthened the role of these two neuropeptides in a range of normal and pathological human behaviors. Importantly, dysfunctions in the OT and AVP neural pathways are likely contributing to deficits in social skills and communication in disorders such as autism. This Research Topic covers the state of the science and provides a deep view of social hormone research in humans to illustrates how pharmacological, genetic and neuroimaging strategies can be successfully combined toward unraveling the mystery of how human social behavior is regulated. Understanding human social behavior at the molecular level, i.e. social neuroscience, is not only crucial for treatment and diagnosis of disorders characterized by deficits in social cognition but also has important implications in establishing the congruence of findings from different approaches in the Social Sciences and Biology. We bring together in this issue a broad spectrum of investigators from the neurosciences, genetics, psychology, economics and political science towards a deeper understanding of the biological roots of human social behavior. We hope that this transdisciplinary Research Topic will bring new insights and ideas to the field, give future perspectives while also addressing open questions and limitation in order to develop intervention and prevention strategies, and to translate the basic social hormone research into clinical applications. This Research Topic covers the state of the science and provides a deep view of social hormone research in humans to illustrates how pharmacological, genetic and neuroimaging strategies can be successfully combined toward unraveling the mystery of how human social behavior is regulated. Understanding human social behavior at the molecular level, aka social neuroscience, is not only crucial for treatment and diagnosis of disorders characterized by deficits in social cognition but such an understanding has important implications for consilience of the Social Sciences and Biology. We bring together in this issue a broad spectrum of investigators from the neurosciences, genetics, psychology, economics and political science towards a deeper understanding of the biological roots of human social behavior. We hope that this transdisciplinary Research Topic will bring new insights and ideas to the field, give future perspectives while also addressing open questions and limitation in order to develop intervention and prevention strategies, and to translate the basic social hormone research into clinical applications.